Construction quality management : principles and practice - Watson, Paul (Paul A.) (Spon Press, 2011)
"Written in line with the ISO 9001:2008 standard, this textbook provides a comprehensive evaluation of quality management systems and tools. Their effectiveness in achieving construction project objectives is explored, as well as applications in corporate performance enhancement for business types across the bult environment. Self test questions and case studies are included to help the student and professional alike"--